Medical Image Encryption and Decryption Based on DNA: A Survey - Saja Theab Ahmed; Dalal Abdulmohsin Hammood; Raad Farhood Chisab; Nurulisma Binti Hj. Ismail (Journal of Techniques)
In the medical field, advanced techniques such as e-health, intelligent health, and telemedicine apps are being deployed. These approaches use open-source networks to send digital medical images. Patients’ private and sensitive diagnosis is contained in the digital medical image. Then sent the digital medical images are used for diagnosis by the remote center. For this reason, protecting patient privacy and the integrity of medical images is of paramount importance. DNA Digital coding is the most popular form of cryptographic technology, and it is frequently employed to strengthen information security, and the most prevalent constraints of DNA cryptographic schemes feature a high degree of temporal and algor. If DNA is employed appropriately, it can be used to achieve a number of security technologies, including encryption, steganography, signature, and authentication through the use of DNA molecules as information carriers. In this paper, a survey on the digital medical image was done. This survey contains the methods of encryption, and decryption of the image which is based on DNA with all the related methods and makes the comparison between the previous papers and explain which is the best to use.